The power of one : how I found the strength to tell the truth and why I blew the whistle on Facebook - Haugen, Frances (Little, Brown and Company, 2023)
"The inside story of one woman's battles against Big Tech, by the Facebook whistleblower who is determined to help us all retake control of our lives. In 2021, when news outlets feasted on "the Facebook Files," Frances Haugen went public as the former employee who blew the whistle on the company by copying tens of thousands of pages of documents. She testified to Congress and spoke to the media. She was hailed at President Biden's first State of the Union Address. She made sure everyone understood exactly what the documents revealed: Facebook knew it had accidentally changed its algorithm to reward extremism and refused to fix it; it knew that its customers were using the platform to foment violence, to spread falsehoods, to diminish the self-esteem of young women, and more. But how was it that Haugen was the only employee at the company who dared to step forward?" --